2017
DOI: 10.1007/s11250-017-1298-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of porcine kobuvirus in piglets in 2009–2013 in northern Thailand

Abstract: A total of 636 fecal samples collected from piglets with and without diarrhea during 2009 to 2013 were tested for porcine kobuvirus by RT-PCR. From a total of 528 fecal samples collected from piglets with diarrhea and 108 from healthy controls, 505 (95.6%) and 104 (96.3%) were positive for porcine kobuvirus, respectively. The detection rates of porcine kobuvirus were remarkable equally high in both diarrheic and healthy piglets. Phylogenetic analysis revealed that porcine kobuvirus strains detected in both sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, only 4% of the diarrhoeic pigs were not co-infected with other pathogens. Recent studies have found the prevalence of PKV-1 to be similar in diarrhoeic and healthy pigs [58][59][60][61], although, two of the studies showed that diarrheic suckling piglets was the most frequently infected group but the results were not statistically significantly different from the healthy piglets [58,59]. Altogether, these finding indicated that PKV-1 is not a significant primary pathogen in natural cases of diarrhoea in young piglets.…”
Section: Discussionmentioning
confidence: 88%
“…However, only 4% of the diarrhoeic pigs were not co-infected with other pathogens. Recent studies have found the prevalence of PKV-1 to be similar in diarrhoeic and healthy pigs [58][59][60][61], although, two of the studies showed that diarrheic suckling piglets was the most frequently infected group but the results were not statistically significantly different from the healthy piglets [58,59]. Altogether, these finding indicated that PKV-1 is not a significant primary pathogen in natural cases of diarrhoea in young piglets.…”
Section: Discussionmentioning
confidence: 88%
“…Porcine Kobuviruses , infecting only pigs, are generally closely related. However, after the discovery of porcine-like Bovine Kobuvirus in pigs, the interspecies transmission of Kobuviruses cannot be excluded ( Chuchaona et al, 2017 ). Porcine Kobuvirus infection in Serbia has never been investigated, though the very high prevalence in the neighboring countries suggests the high likelihood of the presence in Serbia too.…”
mentioning
confidence: 99%
“…Porcine viral diarrhea disease seriously endangers the development of the pig industry, and leads to signi cant economic losses for pig farmers worldwide [7]. Clinically, the complexity of the disease has increased.…”
Section: Discussionmentioning
confidence: 99%